Treatment of Cerebral Venous Sinus Thrombosis : A Nepalese Perspective - Rajbhandari, Reema; Nepal, Medhawee; Panthi, Nabin; Chandra, Avinash; Raghubanshi, Nipun; Shrestha, Tejashwi; Rajbhandari, Pravesh (Annapurna Journal of Health Sciences, 2025)
Introduction: Cerebral venous sinus thrombosis (CVST) is a rare form of stroke, accounting for less than 1% of all cases, with a notable female-to-male ratio of 3:1. It results in venous congestion, increased intracerebral pressure, cerebral edema, and can lead to either cerebral infarction or hemorrhage. Methods: A retrospective study was conducted among patients admitted and diagnosed with CVST at Annapurna Neurological Institute and Allied Sciences from January 2016 to December 2023 Patients with stroke and outpatient department were excluded in the study. The data were entered in MS Excel and descriptive analysis was performed using SPSS Version 25. Results: Out of 66 patients included in the study, majority of the patients were between the age group of 31 to 40 years. Most common presenting features were headache and vomiting (n=43, 65.2%) whereas few (n=10, 15.2%) had symptoms of blurred vision. In this study, 52.1% of patients were admitted due to idiopathic causes. Oral anticoagulants were prescribed and low molecular weight heparin was used for the treatment of CVST. Conclusion: This study provides insight into the epidemiology, clinical outcomes, and risk factors of CVST. Early diagnosis and prompt treatment are crucial for improving patient outcomes. However, the retrospective nature and small sample size limit the findings. Future research should focus on large-scale, prospective studies and explore novel therapeutic strategies.